PENGOLAHAN KOPI ROBUSTA DAN KAJIAN ANALISIS USAHA PADA MANGKUDIRJO COFFEE & ROASTERY - Sri Sari Utami; Nurul Hidayati; Sunar, Sunar (Fakultas Pertanian Universitas Janabadra, 2025)
Robusta coffee is one of the leading commodities with significant economic potential, particularly in tropical regions. This study encompasses the entire processing chain, including sorting coffee fruit, removing the pulp, drying, grinding, and sorting and grading the coffee beans before packing. The aim of this research is to analyze the processing methods of robusta coffee and evaluate the business feasibility of Mangkudirjo Coffee & Roastery. The study utilizes both primary and secondary data. Primary data were gathered through interviews and direct observations, while secondary data were obtained from literature reviews, online sources, and reports from relevant agencies. The economic analysis of the robusta coffee business involved calculating production costs, income, and profits at the scale of small to medium enterprises. The results indicate that, from an economic standpoint, the robusta coffee business is viable, with a monthly profit of IDR 90,721,249. The break-even point (BEP) for production is 2,890 kg, and the BEP price is IDR 24,856 per kg. Additionally, the resource cost (RC) ratio is 1.73, and the return on investment (ROI) is 8.8%. This research is intended to serve as a reference for farmers, business operators, and policymakers in the sustainable development of the robusta coffee industry.